Finding Benefits over Reluctance – Promoting Finnish Trade during African State Visits in Finland in the 1980s - Holmi, Jerkko (Taylor & Francis online, 2025)
In the mid-1980s, Finnish decision-makers pursued a policy of increased trade with the Global South. This article examines the contributions of Finnish policymakers and company representatives to the commercial aspects addressed during the state visits from Africa in the mid-1980s. The article concentrates on the visits of political leaders from Zambia and Tanzania in 1985, and from Kenya in 1987. These visits have been selected due to their temporal proximity, the commercial connotations in the schedule of the visits, the similarity of the visiting states, and the significance of the given Finnish official development assistance (ODA). The findings present answers to the question of what the premises and justifications were for and against these commercial contributions. The article presents an overview of the aspects that were crucial to the decision-making when Finnish actors conducted trade-oriented relations with African states. The findings indicate that despite the initial reluctance to make arrangements, the conducted visits led to an increased promotion of trade-related aspects between Finland and its counterparts. The most crucial achievements were offering Finnish companies a chance to present their knowhow to African political leaders and stimulating discussion between these parties, in conjunction with Finnish policymakers providing their assistance.